MetaboLights: An Open‐Access Database Repository for Metabolomics Data. Issue 1 (24th March 2016) - Kale, Namrata S.; Haug, Kenneth; Conesa, Pablo; Jayseelan, Kalaivani; Moreno, Pablo; Rocca‐Serra, Philippe; Nainala, Venkata Chandrasekhar; Spicer, Rachel A.; Williams, Mark; Li, Xuefei; Salek, Reza M.; Griffin, Julian L.; et al.
Abstract: MetaboLights is the first general purpose, open‐access database repository for cross‐platform and cross‐species metabolomics research at the European Bioinformatics Institute (EMBL‐EBI). Based upon the open‐source ISA framework, MetaboLights provides Metabolomics Standard Initiative (MSI) compliant metadata and raw experimental data associated with metabolomics experiments. Users can upload their study datasets into the MetaboLights Repository. These studies are then automatically assigned a stable and unique identifier (e.g., MTBLS1) that can be used for publication reference. The MetaboLights Reference Layer associates metabolites with metabolomics studies in the archive and is extensively annotated with data fields such as structural and chemical information, NMR and MS spectra, target species, metabolic pathways, and reactions. The database is manually curated with no specific release schedules. MetaboLights is also recommended by journals for metabolomics data deposition. This unit provides a guide to using MetaboLights, downloading experimental data, and depositing metabolomics datasets using user‐friendly submission tools. © 2016 by John Wiley & Sons, Inc.